PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENGUKUR PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SD NEGERI 34 LUBUKLINGGAU - Ayunda, Rani; Asri Purwasi, Lucy; Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract The aim of the research was to determine students' understanding of mathematical concepts at SD Negeri 34 Lubuklinggau after implementing the Contextual Teaching and Learning learning model assisted by Audio Visual Media. The research method is Pre Experiment Design in the form of pretest posttest design. The data collection technique is in the form of essay questions. Data were analyzed using z-test. The understanding of mathematical concepts of fifth grade students at SD Negeri 34 Lubuklinggau after implementing the Contextual Teaching and Learning learning model assisted by Audio Visual media significantly reached the good category. The results of the pre-test calculation of understanding mathematical concepts obtained an average value of 24.21 in the very low category and the results of the post-test calculation of understanding of mathematical concepts obtained an average value of 79.37 in the good category. Based on the results of the z-test analysis at a significant level of α = 0.05, it can be seen that z_count (4.20) ≥ z_tabel (1.64), it can be concluded that students' understanding of mathematical concepts using the Contextual Teaching and Learning learning model assisted by Audio Visual Media is significant reached the good category. Keywords: audio visual media, contextual teaching and learning model, understanding mathematical concepts